Naked eye detection of the Mycobacterium tuberculosis complex by recombinase polymerase amplification—SYBR green I assays - Nuntita Singpanomchai (2020)
© 2018 Wiley Periodicals, Inc. Background: Rapid diagnosis of Mycobacterium tuberculosis (Mtb) is key to controlling the spread of tuberculosis, which is a global health concern. In this study, isothermal recombinase polymerase amplification (RPA) was developed to detect specific targets of Mtb, IS6110 and IS1081. Additionally, SYBR Green I was used for endpoint detection of the RPA products by the naked eye. Method: A total of 146 genomic Mtb DNA samples and 24 genomic nontuberculous mycobacteria (NTM) DNA samples were amplified at IS6110 and IS1081 by RPA. After a complete amplification, the RPA amplicons were examined by agarose gel electrophoresis (RPA-AGE) and SYBR Green I (RPA-S) assays. The performance of the RPA assays was evaluated by comparing them to a conventional PCR. Results: The RPA assay demonstrated to have a good capability to differentiate Mtb from NTM with a very short turnaround time at a constant temperature. Compared to conventional PCR, the sensitivities and specificities of RPA-AGE for IS6110 and IS1081 were 100%. The specificity of RPA-S was 100% for both targets; however, its sensitivities for IS6110 and IS1081 were 97.95% and 99.32%, respectively. The limits of detection of IS6110 RPA-AGE and RPA-S were 0.05 and 0.5 ng, respectively, while the LODs of IS1081 RPA-AGE and RPA-S were 0.00005 and 0.05 ng, respectively. Both RPA assays showed a satisfying diagnostic specificity, with no cross-reaction with other bacteria. Conclusion: A rapid, sensitive, naked eye RPA assay can be integrated into point-of-care diagnosis for Mtb detection, especially in remote areas where laboratory instrument resources are limited.